PRESERVATION OF CULTURAL VALUES THROUGH THE STUDY OF SUMEDANG’S TRADITIONAL WEDDING ATTIRE - Nurhasanah, Nurhasanah; Septiyani, Annisa (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2025)
The purpose of this study is to investigate the cultural meanings and values related to Sumedang’s traditional ancestral wedding clothes. The study used semiotic analysis combined with a qualitative descriptive method to determine the symbolic meanings related to different clothing elements. Experts and pertinent stakeholders were contacted for observations, interviews, and documentation in order to gather data. The results show that every component of the wedding clothes, such as the Siger binokasri and the Binokasih crown, represents certain cultural values including compassion, leadership, and harmony. The study comes to the conclusion that traditional wedding clothing represents Sumedang’s cultural history and is more than simply a trend. Preserving and maintaining these clothes is crucial to raising community awareness and respect for traditional knowledge. Keywords: Semiotics, Traditional wedding clothes, Sumedang, Preserving